Perancangan Sistem Informasi Peminjaman dan Pengembalian Buku dengan Bahasa Pemrograman Visual Basic 6.0 pada Kantor Perpustakaan, Arsip, dan Dokumentasi Kota Padang Panjang - Yaseva, Suci Indah; ardoni, ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
Based on the observation, the book lend and give-back process in the Documentation, Archive, and Library of Padang Panjang was not good enough. The librarians still did simple record by usng Microsoft Excel which record the member data per sheet. This process was found to take long time and was ineffective. It will different if the librarian use the new book lend and give-back information system. The objective of this information system design is to help Documentation, Archive, and Library of Padang Panjang in book lend and give-back process fastly and easily. This design use Visual Basic 6.0 program language. The result of the information system design with Visual Basic 6.0 program language was the process of book lend and give-back process could be done easily since the new system contain Microsoft Access database as an accurate, clear, and originality guaranteed data savings, moreover, the needed information can be seen anytime easily. Keywords: information system; visual basic 6.0